Preparation and Modification of High-Performance Polychlorotrifluoroethylene Through Physical Blending - Yang, Mingming; Xu, Ruoyu; Guo, Shaoyun; Shen, Jiabin (Frontiers in Materials, 2022)
Polychlorotrifluoroethylene (PCTFE) as one of the earliest developed and commercialized fluoropolymers has been used in high-frequency communication, anti-corrosion, and medical packaging fields. However, relatively poor processability and mechanical performances resulted from high molecular regularity and crystallinity limited its broader applications. Herein, the pristine PCTFE was physically modified by blending with its pyrolysis products (FCO). It was demonstrated that the addition of FCO accelerated the molecular relaxation and retarded the crystallization process of PCTFE, leading to the distinct improvement on processability and mechanical performances. When 10% FCO was loaded, the equilibrium torque was decreased by 20%, the elongation at break and impact strength were enhanced by 3.6 and 10.6 times in comparison to those of PCTFE. Additionally, because of the good compatibility of the components, the blend also maintained ultralow dielectric constant/loss, good transparency, and high water-vapor barrier performances. Accordingly, this work paved an effective route to prepare high-performance PCTFE materials, which may play an important role in high-frequency communication field.